(untitled) (Quinto Sol, 2017)
The present paper examines the policies carried out by Minister of Social Welfare, Francisco Manrique throughout the de facto presidencies of Generals Roberto Levingston (1970-1971) and Alejandro Lanusse (1971-1973). I argue that the social policies and strategies implemented by Manrique aimed at building the consensus needed in view of the government’s forthcoming political openness, and at the same time were leaded by his veiled intention of launching his presidential candidacy for the elections that would take place in 1973.